Application of the Think Pair Share Learning Model to Improve Recount Text Reading Skills in Class X-1 SMAN 1 Padangsidimpuan - Torang Siregar (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Abstract This research aims to describe the planning, implementation and evaluation of improving reading skills learning in class X Science 4 students at SMA Negeri 1 Padangsidimpuan using the TPS (Think Pair Share) method. This research is classroom action research (PTK) and the data is presented through qualitative and quantitative descriptive data. This research was carried out in two cycles. Each cycle consists of 4 stages, namely: planning, implementation, action, observation and reflection. learning process data, each cycle is analyzed descriptively qualitatively. Meanwhile, learning outcome data was analyzed quantitatively descriptively. The subjects of this research were 33 students of class X Science 4. The research results showed that the classical completeness score obtained by students in cycle I was 67.83%, while in cycle II it reached 85.67%. The research results show that learning using the TPS method can improve reading skills, especially historical recount texts, for students in class X Science 4 at SMA Negeri 1 Padangsidimpuan.